A modifier for a modified polyester powder coating and a method for preparing the same
Patent Information
- Application Number
- CN202611071256.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2046-07-20
AI Technical Summary
但普通无机粒子表面极性较强,与聚酯-环氧固化体系相容性和反应结合能力有限,易在加工和固化过程中出现团聚、界面结合不足或折射率不匹配等问题,进而影响涂层性、光泽度和外观均匀性
1.本发明所述的改性剂以纳米二氧化硅作为无机核体,并通过苯基三甲氧基硅烷、γ-缩水甘油醚氧丙基三甲氧基硅烷和3-氨丙基三乙氧基硅烷进行表面硅烷化改性,在粒子表面引入苯基、环氧基和氨基等功能结构,形成折射率梯度调节层,提高了改性剂与聚酯-环氧固化体系的相容性和分散均匀性,有利于保持粉末涂层的透光率、光泽度及外观均匀性。
Smart Images

Figure CN122628642B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of powder coating technology, and more specifically to a modifier for modified polyester powder coatings and its preparation method. Background Technology
[0002] Powder coatings are a type of solid powder coating material, characterized by high coating efficiency, recyclability, and environmental friendliness. They are widely used in metal products, appliance casings, building profiles, and decorative protective coatings. While providing protection, powder coatings can preserve the surface texture, metallic feel, or base color of the substrate. Therefore, high requirements are placed on the coating's light transmittance, gloss, adhesion, and impact resistance.
[0003] Polyester powder coatings typically consist of a film-forming acid component and an epoxy curing component, which are melt-extruded, pulverized and sieved, electrostatically sprayed, and heat-cured to form a coating. To improve their overall performance, existing technologies often incorporate functional components such as nano-silica, antioxidants, light stabilizers, and leveling agents. However, ordinary inorganic particles have strong surface polarity and limited compatibility and reactive bonding with the polyester-epoxy curing system. This can easily lead to problems such as agglomeration, insufficient interfacial bonding, or refractive index mismatch during processing and curing, thus affecting coating properties, gloss, and appearance uniformity.
[0004] Therefore, it is necessary to provide a reactive multilayer core-shell hybrid modifier suitable for polyester powder coating systems. Through structural design such as refractive index gradient adjustment, phosphorus-nitrogen-zinc-aluminum coordination, and aromatic dianhydride interface locking, the modifier can improve the dispersion stability and interfacial bonding performance in the system, thereby improving the mechanical properties and adhesion performance of the coating while maintaining coating properties and gloss. Summary of the Invention
[0005] The purpose of this invention is to address the need for improvements in the dispersion uniformity of inorganic modified components, interfacial bonding of the polyester-epoxy system, coating properties, gloss, impact resistance, and adhesion of existing polyester powder coatings, by providing a modified polyester powder coating and its preparation method. The aim is to improve the compatibility and interfacial bonding between the modifier and the polyester-epoxy curing system by constructing a reactive multilayer core-shell hybrid modifier with a refractive index gradient adjusting layer, a phosphorus-nitrogen-zinc-aluminum coordination inner shell layer, and a reactive aromatic dianhydride interfacial locking outer shell layer. This enhances the dispersion stability of the inorganic modified components, reduces the impact of particle agglomeration and interfacial defects on coating performance, thereby improving the coating's properties, gloss, impact resistance, and adhesion.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A modified polyester powder coating, by weight, comprises the following components: 80-120 parts of film-forming acid component; 155-190 parts of epoxy curing component; 0.6-2.0 parts of modifier; 0.8-1.5 parts of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate; 0.3-0.6 parts of antioxidant; 0.3-0.8 parts of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate; and 0.05-0.12 parts of triphenylphosphine.
[0007] The film-forming acid component and the epoxy curing component are combined according to the principle of moderate excess of epoxy groups, so that the epoxy groups participate in the ring-opening curing of acid-epoxy and further participate in the ring-opening cross-linking reaction under the catalysis of triphenylphosphine.
[0008] Furthermore, the modifier is a reactive multilayer core-shell hybrid modifier having a refractive index gradient regulating layer, a phosphorus-nitrogen-zinc-aluminum coordination inner shell layer, and a reactive aromatic dianhydride interface-locked outer shell layer.
[0009] Furthermore, the modifier is made from the following raw materials in parts by weight: 42-50 parts of nano silica, 8-18 parts of phenyltrimethoxysilane, 14-28 parts of γ-glycidyl etheroxypropyltrimethoxysilane, 3-9 parts of 3-aminopropyltriethoxysilane, 6-15 parts of phytic acid, 9-18 parts of melamine, 6-14 parts of zinc acetate dihydrate, 3-8 parts of aluminum nitrate nonahydrate, 3-9 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid, 4-12 parts of pyromellitic dianhydride, and 0.08-0.25 parts of triphenylphosphine.
[0010] Furthermore, the preparation method of the modifier includes the following steps: S1. The nano-silica is dried at 115-130℃ for 2-5 hours, and 240-560 parts of anhydrous ethanol and 80-240 parts of deionized water are added to form a solid-liquid dispersion system. The pH is adjusted to 8.6-9.6 with 25% ammonia water by mass. The mixture is stirred at 38-48℃ and 900-1400r / min for 35-70 minutes, and then ultrasonically dispersed at 20-28kHz for 20-40 minutes to obtain a nano-silica dispersion.
[0011] S2. Take the nano-silica dispersion and adjust the pH to 6.5-7.0 with 5% (w / w) dilute acetic acid. Dissolve phenyltrimethoxysilane and γ-glycidoxypropyltrimethoxysilane in 40-110 parts anhydrous ethanol and 10-35 parts deionized water, add glacial acetic acid to adjust the pH to 4.1-4.5, and hydrolyze at 28-38℃ for 30-50 min to obtain an epoxysilane hydrolysate. Add the hydrolysate dropwise to the adjusted silica dispersion at 0.5-1.0 mL / min, and continuously add 5% (w / w) ammonia water at a rate of 0.1-0.3 mL / min to the system. The pH was controlled at 6.5-7.2. After the addition was completed, the mixture was reacted at 62-76℃ for 2-3 hours to obtain an epoxy-phenyl modified slurry. Separately, 3-aminopropyltriethoxysilane was dissolved in 40-110 parts of anhydrous ethanol and 10-35 parts of deionized water, the pH was adjusted to 4.5-5.0, hydrolyzed at 25-35℃ for 30 minutes, and added dropwise to the above slurry at 0.2-0.5 mL / min. The reaction was continued at 55-65℃ for 1.5-2.5 hours. The mixture was filtered, and the filter cake was washed 2-4 times with 100-200 parts of anhydrous ethanol until the pH of the final washing filtrate was 6.6-7.4, to obtain a silanized nano-silica wet filter cake.
[0012] S3. Add the melamine to 60-160 parts of deionized water, stir for 30-55 min at 78-90℃ and 650-950 r / min, adjust the pH of the system to 4.9-5.7 with glacial acetic acid, and then add the silanized nano-silica wet filter cake; prepare the phytic acid into a phytic acid aqueous dispersion with a mass fraction of 40-60%, and add the phytic acid aqueous dispersion dropwise to the system at a rate of 0.25-0.75 mL / min. After the addition is complete, maintain the temperature for 60-100 min. Subsequently, the zinc acetate dihydrate and aluminum nitrate nonahydrate were added to 40-220 parts of deionized water to prepare a metal salt dispersion with a total mass fraction of 8-16%. The metal salt dispersion was added dropwise to the system at a rate of 0.15-0.55 mL / min. The pH of the system was maintained at 5.3-6.1 using 25% ammonia water. The reaction was continued at 80-88℃ for 2-4 hours. The mixture was then filtered and washed with deionized water until the conductivity of the filtrate was no higher than 70 μS / cm, yielding a composite particle wet filter cake.
[0013] S4. The composite particle wet filter cake obtained in step S3 is dried at 90-110℃ and vacuum degree of -0.085MPa for 2-4h and then dispersed in 160-360 parts of butyl acetate. The 3,5-di-tert-butyl-4-hydroxybenzoic acid and triphenylphosphine are added, and the mixture is heated to 95-108℃ under nitrogen protection and stirred at 700-1000r / min for 1.5-3h to obtain the composite particle dispersion system.
[0014] S5. Add pyromellitic dianhydride to the composite particle dispersion system, controlling the mass ratio of composite particles to pyromellitic dianhydride to be 1:0.04-1:0.16, and continue the reaction for 3-6 hours under nitrogen protection at 105-118℃ and 850-1250 r / min. Then, rotary evaporate under reduced pressure at -0.080-0.095 MPa to obtain a wet multilayer core-shell hybrid composite.
[0015] S6. The wet multilayer core-shell hybrid composite is dried at 58-72°C and a vacuum degree not higher than -0.085MPa for 9-16 hours, then pulverized by airflow and sieved to pass through a 1200-1800 mesh sieve to obtain the modifier.
[0016] Furthermore, the film-forming acid component is selected from one or more of 1,4-cyclohexanedicarboxylic acid, sebacic acid, and trimellitic anhydride.
[0017] Furthermore, the epoxy curing component is selected from one or two of triglycidyl isocyanurate and trimethylolpropane triglycidyl ether.
[0018] Furthermore, the antioxidant is selected from one or two of 2,6-di-tert-butyl-4-methylphenol and triphenyl phosphite.
[0019] This invention also provides a method for preparing a modified polyester powder coating, comprising the following steps: A1. The film-forming acid component, epoxy curing component, modifier, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, antioxidant, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate and triphenylphosphine are added to a high-speed mixer and premixed at 600-1200 r / min for 6-15 min to obtain a premix.
[0020] A2. The premixed material is added to a twin-screw extruder for melt extrusion. The temperature of the twin-screw extruder is 75-90℃ in zone 1, 90-105℃ in zone 2, 100-115℃ in zone 3, and 95-110℃ at the die head. The screw speed is 180-350 r / min, and the material residence time is 45-120 s to obtain the melt extrudate.
[0021] A3. The molten extrudate is cooled by pressing, with the temperature of the cooling roller controlled at 10-25℃ and the sheet thickness at 0.8-2.0mm. After cooling, it is crushed to obtain sheet material.
[0022] A4. The sheet material is pulverized by airflow or mechanical pulverization and then sieved to remove coarse powder that does not pass through a 120-mesh sieve and fine powder that passes through a 200-mesh sieve. The powder that passes through a 120-mesh sieve but does not pass through a 200-mesh sieve is collected to obtain modified polyester powder coating.
[0023] A5. Electrostatically spray the modified polyester powder coating onto the surface of a metal substrate that has been degreased, derusted, or phosphated. The spraying voltage is 40-80kV, the coating thickness is 60-100μm, and the coating is cured at 180-200℃ for 10-20min to obtain the modified polyester powder coating.
[0024] Further, in step A2, the modifier and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate are first added to a pre-dispersion container and pre-dispersed at 300-700 r / min for 4-10 min.
[0025] Furthermore, in step A3, the molten extrudate is introduced into a cooling tableting device for tableting and cooling within 30 seconds. The cooling roller temperature of the cooling tableting device is 8-22℃, the roller spacing is 0.6-1.5mm, and the tableting roller speed is 12-35r / min.
[0026] Furthermore, in step A4, the sheet material obtained in step A3 is subjected to airflow pulverization under the conditions of an inlet air temperature of 10-25℃, a classifying wheel speed of 1800-3200 r / min, and a pulverizing pressure of 0.45-0.75 MPa.
[0027] This invention constructs a basic curing system for polyester powder coatings using a film-forming acid component and an epoxy curing component. A dense coating network is formed through the cross-linking curing reaction between the acid and epoxy components. Secondly, nano-silica is used as an inorganic core, and its surface is modified with phenyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and 3-aminopropyltriethoxysilane to introduce active groups onto the particle surface, thus adjusting its compatibility and reactivity with the polyester-epoxy system. Simultaneously, a phosphorus-nitrogen-zinc-aluminum complex is constructed using phytic acid, melamine, zinc salts, and aluminum salts. The inner shell layer, in conjunction with 3,5-di-tert-butyl-4-hydroxybenzoic acid and pyromellitic dianhydride, forms a reactive aromatic dianhydride interface-locked outer shell layer, enabling the modifier to form a reactive multilayer core-shell hybrid structure with a refractive index gradient adjustment layer, a coordination inner shell layer, and a reactive outer shell layer. Finally, in conjunction with components such as 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, antioxidants, hindered amine light stabilizers, and triphenylphosphine, it plays a role in dispersion regulation, curing promotion, and interfacial bonding, ultimately giving the obtained polyester powder coating good properties, gloss, impact resistance, and adhesion.
[0028] Compared with the prior art, the beneficial effects of the present invention are: 1. The modifier of the present invention uses nano-silica as an inorganic core and undergoes surface silanization modification through phenyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane and 3-aminopropyltriethoxysilane. Functional structures such as phenyl, epoxy and amino groups are introduced on the particle surface to form a refractive index gradient adjustment layer, which improves the compatibility and dispersion uniformity of the modifier with the polyester-epoxy curing system and is beneficial to maintaining the light transmittance, gloss and appearance uniformity of the powder coating.
[0029] 2. The modifier of this invention constructs a phosphorus-nitrogen-zinc-aluminum coordination inner shell layer on the surface of silanized nano-silica using phytic acid, melamine, zinc acetate dihydrate, and aluminum nitrate nonahydrate, thereby enabling the modifier to form a stable hybrid structure in the coating system. This structure enhances the interfacial bonding effect between inorganic components and organic resins and is beneficial for improving the dispersion and interfacial bonding state of the modifier in the coating system.
[0030] 3. The modifier of the present invention further employs 3,5-di-tert-butyl-4-hydroxybenzoic acid and pyromellitic dianhydride to perform interface modification on the composite particles, forming a reactive aromatic dianhydride interface-locking shell layer on the particle surface. This allows the modifier to participate in the construction of the curing network of the polyester-epoxy system, improving the interfacial bonding strength, impact resistance, and adhesion of the coating. Simultaneously, the combination of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate and triphenylphosphine and other components helps improve the leveling properties and interfacial bonding effect of the powder coating during melt extrusion and curing film formation. Attached Figure Description
[0031] Figure 1 This is a SEM image of the preparation of the modifier obtained in Example 1 of the present invention. Detailed Implementation
[0032] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0033] Preparation Example 1 Preparation of modifier: 1. Raw material weight parts: Nano silica: 46 parts; phenyltrimethoxysilane: 12 parts; γ-glycidoxypropyltrimethoxysilane: 20 parts; 3-aminopropyltriethoxysilane: 6 parts; phytic acid: 10 parts; melamine: 14 parts; zinc acetate dihydrate: 10 parts; aluminum nitrate nonahydrate: 5 parts; 3,5-di-tert-butyl-4-hydroxybenzoic acid: 6 parts; pyromellitic dianhydride: 7 parts; triphenylphosphine: 0.16 parts; anhydrous ethanol: 470 parts; deionized water: 410 parts.
[0034] 2. Preparation method: S1. Take nano-silica and dry it at 120℃ for 3h. Add the dried nano-silica to 350.0 parts of anhydrous ethanol and 150.0 parts of deionized water to form a dispersion system with a solid-liquid mass ratio of 1:10.87. Add 25% ammonia water to adjust the pH of the system to 9.1. Stir at 43℃ and 1100r / min for 50min, and then disperse it by ultrasonication at 24kHz for 30min to obtain a nano-silica dispersion.
[0035] S2. Add 5% (w / w) dilute acetic acid to the nano-silica dispersion to adjust the pH of the system to 6.8. Add phenyltrimethoxysilane and γ-glycidoxypropyltrimethoxysilane to 70.0 parts anhydrous ethanol and 20.0 parts deionized water, adjust the pH to 4.3 with glacial acetic acid, and hydrolyze at 33℃ for 40 min to obtain phenyl-epoxysilane hydrolysate. Add the phenyl-epoxysilane hydrolysate dropwise to the adjusted nano-silica dispersion at a rate of 0.7 mL / min. During the dropwise addition, maintain the pH of the system at 6.8-7.0 with 5% (w / w) ammonia. After the dropwise addition is completed, raise the temperature to 70℃ and maintain the pH at 900 r / min. The reaction was carried out for 2.5 h under the specified conditions to obtain an epoxy-phenyl modified slurry. Separately, 3-aminopropyltriethoxysilane was added to 50.0 parts of anhydrous ethanol and 20.0 parts of deionized water, and glacial acetic acid was added to adjust the pH to 4.8. The mixture was hydrolyzed at 30 °C for 30 min to obtain an aminosilane hydrolysate. The aminosilane hydrolysate was added dropwise to the epoxy-phenyl modified slurry at a rate of 0.35 mL / min, and the reaction was continued at 60 °C and 850 r / min for 2 h. After the reaction was completed, the mixture was filtered, and the filter cake was washed twice with 100.0 parts of anhydrous ethanol, 50.0 parts of anhydrous ethanol each time, until the pH of the filtrate was 6.9, to obtain a silanized nano-silica wet filter cake.
[0036] S3. Add the melamine to 100.0 parts of deionized water and stir for 45 min at 85°C and 800 r / min. Adjust the pH of the system to 5.3 with 2.5 parts of glacial acetic acid, then add all the silanized nano-silica wet filter cake obtained in step S2. Take 10.0 parts of phytic acid and add it to 10.0 parts of deionized water to prepare a 50% (w / w) phytic acid aqueous dispersion. Add the phytic acid aqueous dispersion dropwise to the system at a rate of 0.50 mL / min. After the addition is complete, keep the system at 85°C for 80 min. Then add zinc acetate dihydrate and... Aluminum nitrate nonahydrate was added to 110.0 parts of deionized water to prepare a metal salt dispersion with a total mass fraction of 12.0%. The metal salt dispersion was added dropwise to the system at a rate of 0.35 mL / min. During the dropwise addition, 25% ammonia water was added to maintain the pH of the system at 5.7. The reaction was continued for 3 hours at 84℃ and 850 r / min. The mixture was filtered, and the filter cake was washed three times with 300.0 parts of deionized water, with 100.0 parts of deionized water used for each wash, until the conductivity of the final filtrate was 58 μS / cm, thus obtaining a composite particle wet filter cake.
[0037] S4. The wet filter cake of the composite particles is dried at 100°C and a vacuum of -0.085 MPa for 3 hours to obtain dried composite particles with a water content of 0.82 wt%. The dried composite particles are added to 240.0 parts of butyl acetate and stirred and dispersed at 800 r / min for 30 minutes under nitrogen protection to obtain a butyl acetate dispersion of composite particles. 3,5-di-tert-butyl-4-hydroxybenzoic acid and triphenylphosphine are added to the butyl acetate dispersion of composite particles, and the mixture is heated to 102°C under nitrogen protection and stirred at 900 r / min for 2 hours to graft 3,5-di-tert-butyl-4-hydroxybenzoic acid onto the surface of the composite particles through a carboxyl-epoxy ring-opening esterification reaction to obtain a composite particle dispersion system.
[0038] S5. Add pyromellitic dianhydride to the composite particle dispersion system described in step S5, controlling the mass ratio of composite particles to pyromellitic dianhydride to be 1:0.09; heat to 112℃ under nitrogen protection, stir at 1000 r / min for 4 h, so that the pyromellitic dianhydride reacts with the amino, hydroxyl and residual epoxy groups on the surface of the composite particles to undergo ring-opening amidation, esterification or ring-opening addition reactions, forming a reactive aromatic dianhydride interface locking shell layer on the surface of the composite particles; after the reaction is completed, remove butyl acetate under reduced pressure at 80℃ and -0.090 MPa for 90 min to obtain a wet multilayer core-shell hybrid composite.
[0039] S6. The wet multilayer core-shell hybrid composite obtained in step S5 is dried at 65°C and a vacuum of -0.090 MPa for 12 hours to obtain a dried hybrid composite. The dried hybrid composite is then subjected to air jet milling and sieved through a 1500-mesh sieve to obtain a modifier.
[0040] Depend on Figure 1 As can be seen from the SEM image, the modifier obtained in Preparation Example 1 exhibits a typical nanoparticle aggregation morphology. The particles are mainly nearly spherical or quasi-spherical in shape, with a primary particle size of about 80-150 nm, and locally reaching about 200 nm. They form secondary aggregation structures in the range of 0.3-1.0 μm through weak interactions. The particle surface shows obvious roughening and layered coating characteristics, indicating that the nano-silica core has successfully constructed a multi-layer core-shell structure consisting of a silanized modified layer, a phosphorus-nitrogen-zinc-aluminum coordinated inner shell layer, and a pyromellitic dianhydride reactive outer shell layer. At the same time, the overall dispersion is good and no large-scale dense hard agglomerates have appeared, indicating that the modified particles have good interfacial compatibility and structural stability with the organic polyester-epoxy system.
[0041] Comparative Preparation Example 1 The modifier was prepared according to the preparation method in Preparation Example 1, except that 46 parts of nano-silica were replaced with 46 parts of boehmite, and the rest remained the same as in Preparation Example 1.
[0042] Comparative Preparation Example 2 The modifier was prepared according to the preparation method in Preparation Example 1, except that 12 parts of phenyltrimethoxysilane were replaced with 12 parts of methyltrimethoxysilane, and the rest remained the same as in Preparation Example 1.
[0043] Comparative preparation example 3 The modifier was prepared according to the preparation method in Preparation Example 1, except that 6 parts of 3-aminopropyltriethoxysilane were replaced with 6 parts of 3-mercaptopropyltrimethoxysilane, and the rest remained the same as in Preparation Example 1.
[0044] Comparative preparation example 4 The modifier was prepared according to the preparation method in Preparation Example 1, except that 14 parts of melamine were replaced with 14 parts of urea, and the rest remained the same as in Preparation Example 1.
[0045] Comparative preparation example 5 The modifier was prepared according to the preparation method in Preparation Example 1, except that 6 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid were replaced with 6 parts of 2,6-di-tert-butyl-4-methylphenol, and the rest remained the same as in Preparation Example 1.
[0046] Comparative preparation example 6 The modifier was prepared according to the preparation method in Preparation Example 1, except that 7 parts of pyromellitic dianhydride were replaced with 7 parts of trimellitic anhydride, and the rest remained the same as in Preparation Example 1.
[0047] Example 1
[0048] Preparation of a modified polyester powder coating: 1. Raw material weight parts: Film-forming acid component: 100 parts, consisting of 70 parts of 1,4-cyclohexanedicarboxylic acid, 25 parts of sebacic acid, and 5 parts of trimellitic anhydride.
[0049] The epoxy curing component consists of 170 parts, comprising 150 parts of triglycidyl isocyanurate and 20 parts of trimethylolpropane triglycidyl ether.
[0050] Modifier: 1.2 parts, which is the modifier prepared in Preparation Example 1.
[0051] 2,2,4-Trimethyl-1,3-pentanediol diisobutyrate: 1.1 parts.
[0052] Antioxidant: 0.45 parts, consisting of 0.30 parts of 2,6-di-tert-butyl-4-methylphenol and 0.15 parts of triphenyl phosphite.
[0053] Bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate: 0.55 parts.
[0054] Triphenylphosphine: 0.08 parts.
[0055] 2. Preparation method: A1. The film-forming acid component, epoxy curing component, modifier obtained in Preparation Example 1, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, antioxidant, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate and triphenylphosphine are added to a high-speed mixer and premixed at 900 r / min for 10 min, with the material temperature controlled at 40°C during the premixing process to obtain a premix.
[0056] A2. The premixed material is added to a twin-screw extruder for melt extrusion. The temperature of the twin-screw extruder is 82°C in zone 1, 98°C in zone 2, 108°C in zone 3, and 103°C at the die head. The screw speed is 260 r / min and the material residence time is 80 s to obtain the melt extrudate.
[0057] A3. The molten extrudate is fed into a cooling and tableting device within 30 seconds for tableting and cooling. The temperature of the cooling roller is controlled at 16°C, the roller spacing is 1.0 mm, the tableting roller speed is 24 r / min, and the sheet thickness is 1.2 mm. After the sheet is cooled to 28°C, it is crushed at a crushing speed of 1200 r / min for 40 seconds to obtain sheet material.
[0058] A4. The sheet material is subjected to airflow pulverization under the conditions of an inlet air temperature of 18℃, a classifying wheel speed of 2500r / min, and a pulverizing pressure of 0.60MPa. After pulverization, it is sieved using a 120-mesh sieve and a 200-mesh sieve to remove coarse powder that does not pass through the 120-mesh sieve and fine powder that passes through the 200-mesh sieve. The powder that passes through the 120-mesh sieve but does not pass through the 200-mesh sieve is collected to obtain the modified polyester powder coating.
[0059] A5. The modified polyester powder coating is electrostatically sprayed onto the surface of a metal substrate that has been degreased, derusted and phosphated. The spraying voltage is 60kV, the spraying distance is 180mm, the compressed air pressure is 0.30MPa, the coating thickness is 80μm, and it is cured at 190℃ for 15min and cooled to room temperature to obtain the modified polyester powder coating.
[0060] Note: In this embodiment, the film-forming acid component and the epoxy curing component are mixed according to the functional group equivalent ratio, with a slight excess of epoxy groups. During the curing process, carboxyl groups / anhydrides preferentially undergo ring-opening reactions with epoxy to form the main cross-linked network. A small amount of residual epoxy further cross-links under the catalysis of triphenylphosphine and undergoes interfacial reactions with the active groups of the modifier, thereby improving the cross-linking integrity and interfacial bonding, and avoiding excessive residual functional groups from affecting the coating's water resistance, toughness, and other related properties.
[0061] Example 2
[0062] A modified polyester powder coating was prepared by referring to the preparation method in Example 1, except that the mass fraction of the film-forming acid component was replaced with 120 parts, and the rest remained the same as in Example 1.
[0063] Example 3
[0064] A modified polyester powder coating was prepared by referring to the preparation method in Example 1, except that the mass fraction of the epoxy curing component was replaced with 190 parts, and the rest remained the same as in Example 1.
[0065] Example 4
[0066] The preparation of a modified polyester powder coating is carried out by referring to the preparation method in Example 1, except that the mass fraction of the modifier is replaced with 2 parts, and everything else remains the same as in Example 1.
[0067] Example 5
[0068] A modified polyester powder coating was prepared by referring to the preparation method in Example 1, except that the mass fraction of the antioxidant was replaced with 0.6 parts, and everything else remained the same as in Example 1.
[0069] Example 6
[0070] A modified polyester powder coating was prepared by referring to the preparation method in Example 1, except that the mass fraction of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate was replaced with 1.5 parts, and the rest remained the same as in Example 1.
[0071] Comparative Examples 1-6 A modified polyester powder coating was prepared by referring to the preparation method in Example 1, except that the modifier was replaced with the modifier prepared in Comparative Preparation Examples 1-6, and everything else remained the same as in Example 1.
[0072] Comparative Example 7 A modified polyester powder coating was prepared according to the preparation method in Example 1, but without adding the modifier, and otherwise remained the same as in Example 1.
[0073] Performance testing: The modified polyester powder coatings obtained in Examples 1-6 and Comparative Examples 1-7 were used to prepare coating samples for testing. The sample used for coating transmittance testing used a 2.0 mm thick glass plate as the substrate; the sample used for coating gloss, coating impact strength, and coating adhesion testing used a 0.8 mm thick cold-rolled steel plate as the substrate. The cold-rolled steel plate underwent degreasing, rust removal, and phosphating treatments before spraying. Each powder coating was electrostatically sprayed onto the corresponding substrate surface at a spraying voltage of 60 kV, a spraying distance of 180 mm, and a compressed air pressure of 0.30 MPa. The cured coating thickness was controlled to be 80 ± 5 μm. The coating was cured at 190 °C for 15 min, cooled to room temperature, and then placed in an environment with a temperature of 23 ± 2 °C and a relative humidity of 50 ± 5% for 24 h to obtain the coating samples for testing.
[0074] 1. Coating transmittance performance test: The transmittance of the coating was measured using a visible light spectrophotometer in the visible light band (380-780nm), and the transmittance data at a wavelength of 550nm was recorded. Before the test, an uncoated glass plate of the same thickness and material was used as a blank reference sample for calibration. The test results are expressed as a percentage, and the results are shown in Table 1.
[0075] 2. Coating Gloss (60°) Performance Test: The gloss of the coating sample was tested using a 60° gloss meter. The 60° gloss meter was calibrated using a standard black glass plate before testing. The test results are expressed in GU, and are shown in Table 1.
[0076] 3. Using an impact testing apparatus (8.00 mm diameter punch, 1.00 kg weight), place the coating sample to be tested on the impact testing device, allowing the punch to strike the front of the coating. The weight height starts at 10 cm and increases gradually in 5 cm increments. After each impact, observe the impact area to see if cracks, peeling, or exposure of the substrate appear in the coating. The impact strength is expressed as the maximum height (cm) that does not cause cracks, peeling, or exposure of the substrate. The results are expressed in kg·cm (kg·cm = weight kg × height cm), as shown in Table 1.
[0077] 4. Coating Adhesion Performance Test: The coating adhesion of the test samples was tested using the cross-cut method. During the test, six cut lines were made on the coating surface in mutually perpendicular directions with a cut spacing of 2 mm, so that the cuts penetrated the coating to the metal substrate. Then, a 25 mm wide pressure-sensitive adhesive tape was applied to the cut area and pressed evenly along the tape surface for 90 seconds. After pressing, the tape was continuously peeled off at an angle of approximately 60° within 1 second, and the coating peeling in the cut area was observed. The coating was rated from 0 to 5, and the results are shown in Table 1.
[0078] Table 1. Results of performance test data
[0079] The results in the table show that, under the same spraying, curing, and humidity conditioning conditions, the coatings obtained in Examples 1-6 exhibit a relatively coordinated performance distribution in terms of light transmittance, haze, gloss, impact strength, adhesion, abrasion resistance, thermal stability, aging resistance, corrosion resistance, and water absorption. This is because, after phenyl, epoxy, and aminosilanization treatment, nano-silica forms a refractive index gradient regulating layer in the polyester-epoxy curing system, reducing the optical difference between the inorganic and resin phases and improving particle dispersion stability and interfacial compatibility. The phosphorus-nitrogen-zinc-aluminum coordination inner shell layer formed by phytic acid, melamine, zinc salts, and aluminum salts enhances the thermal stability and barrier effect of the coating curing network, increasing the diffusion paths of moisture, salt spray media, and aging factors into the coating interior. The reactive interfacial locking outer shell layer formed by 3,5-di-tert-butyl-4-hydroxybenzoic acid and pyromellitic dianhydride participates in the acid-epoxy crosslinking reaction, enhancing the interfacial bonding between inorganic particles and organic resins, thereby maintaining good levels of impact strength, adhesion, and abrasion resistance. In the comparative examples, changes were made to the core, silane structure, amino reaction sites, phosphorus and nitrogen coordination components, hindered phenolic carboxylic acid structure, and aromatic dianhydride shell structure, or the removal of modifiers and pre-dispersion auxiliary components. The refractive index matching, interfacial reaction, dispersion uniformity, and barrier structure of the coating were all affected to varying degrees.
[0080] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A modified polyester powder coating, characterized in that, By weight, it includes the following raw materials: 80-120 parts of film-forming acid component; 155-190 parts of epoxy curing component; 0.6-2.0 parts of modifier; 0.8-1.5 parts of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate; 0.3-0.6 parts of antioxidant; 0.3-0.8 parts of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate; and 0.05-0.12 parts of triphenylphosphine. The modifier is a reactive multilayer core-shell hybrid modifier having a refractive index gradient regulating layer, a phosphorus-nitrogen-zinc-aluminum coordination inner shell layer, and a reactive aromatic dianhydride interface-locked outer shell layer. The modifier is made from the following raw materials in parts by weight: 42-50 parts of nano silica, 8-18 parts of phenyltrimethoxysilane, 14-28 parts of γ-glycidyl etheroxypropyltrimethoxysilane, 3-9 parts of 3-aminopropyltriethoxysilane, 6-15 parts of phytic acid, 9-18 parts of melamine, 6-14 parts of zinc acetate dihydrate, 3-8 parts of aluminum nitrate nonahydrate, 3-9 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid, 4-12 parts of pyromellitic dianhydride, and 0.08-0.25 parts of triphenylphosphine. The preparation method of the modifier includes the following steps: S1. The nano-silica is dried at 115-130℃ for 2-5 hours, and 240-560 parts of anhydrous ethanol and 80-240 parts of deionized water are added to form a solid-liquid dispersion system. The pH is adjusted to 8.6-9.6 with 25% ammonia water by mass. The mixture is stirred at 38-48℃ and 900-1400 r / min for 35-70 minutes, and then ultrasonically dispersed at 20-28 kHz for 20-40 minutes to obtain a nano-silica dispersion. S2. Take the nano-silica dispersion and adjust the pH to 6.5-7.0 with 5% (w / w) dilute acetic acid. Dissolve phenyltrimethoxysilane and γ-glycidoxypropyltrimethoxysilane in 40-110 parts anhydrous ethanol and 10-35 parts deionized water, add glacial acetic acid to adjust the pH to 4.1-4.5, and hydrolyze at 28-38℃ for 30-50 min to obtain an epoxysilane hydrolysate. Add the hydrolysate dropwise to the adjusted nano-silica dispersion at 0.5-1.0 mL / min, and continuously add 5% (w / w) ammonia water at a rate of 0.1-0.3 mL / min. The pH was controlled at 6.5-7.
2. After the addition was completed, the mixture was reacted at 62-76℃ for 2-3 hours to obtain an epoxy-phenyl modified slurry. Separately, 3-aminopropyltriethoxysilane was dissolved in 40-110 parts of anhydrous ethanol and 10-35 parts of deionized water, the pH was adjusted to 4.5-5.0, hydrolyzed at 25-35℃ for 30 minutes, and added dropwise to the above slurry at 0.2-0.5 mL / min. The reaction was continued at 55-65℃ for 1.5-2.5 hours. The mixture was filtered, and the filter cake was washed 2-4 times with 100-200 parts of anhydrous ethanol until the pH of the final washing filtrate was 6.6-7.4, to obtain a silanized nano-silica wet filter cake. S3. Add the melamine to 60-160 parts of deionized water, stir for 30-55 min at 78-90℃ and 650-950 r / min, adjust the pH of the system to 4.9-5.7 with glacial acetic acid, and then add the silanized nano-silica wet filter cake; prepare the phytic acid into a phytic acid aqueous dispersion with a mass fraction of 40-60%, and add the phytic acid aqueous dispersion dropwise to the system at a rate of 0.25-0.75 mL / min. After the addition is complete, maintain the temperature for 60-100 min. Subsequently, the zinc acetate dihydrate and aluminum nitrate nonahydrate were added to 40-220 parts of deionized water to prepare a metal salt dispersion with a total mass fraction of 8-16%. The metal salt dispersion was added dropwise to the system at a rate of 0.15-0.55 mL / min. The pH of the system was maintained at 5.3-6.1 using ammonia water with a mass fraction of 25%. The reaction was continued at 80-88℃ for 2-4 hours. The mixture was then filtered and washed with deionized water until the conductivity of the filtrate was no higher than 70 μS / cm, resulting in a composite particle wet filter cake. S4. The composite particle wet filter cake obtained in step S3 is dried at 90-110℃ and vacuum degree of -0.085MPa for 2-4h and then dispersed in 160-360 parts of butyl acetate. The 3,5-di-tert-butyl-4-hydroxybenzoic acid and triphenylphosphine are added, and the mixture is heated to 95-108℃ under nitrogen protection and stirred at 700-1000r / min for 1.5-3h to obtain the composite particle dispersion system. S5. Add pyromellitic dianhydride to the composite particle dispersion system, and control the mass ratio of composite particles to pyromellitic dianhydride to be 1:0.04-1:0.
16. Continue the reaction for 3-6 hours under nitrogen protection at 105-118℃ and 850-1250 r / min. Then, rotary evaporate under reduced pressure at -0.080 to -0.090 MPa to obtain a wet multilayer core-shell hybrid composite. S6. The wet multilayer core-shell hybrid composite is dried at 58-72°C and vacuum degree not higher than -0.085MPa for 9-16 hours, then pulverized by airflow and sieved to pass through a 1200-1800 mesh sieve to obtain the modifier. The film-forming acid component is selected from one or more of 1,4-cyclohexanedicarboxylic acid, sebacic acid, and trimellitic anhydride; The epoxy curing components are triglycidyl isocyanurate and trimethylolpropane triglycidyl ether.
2. The modified polyester powder coating according to claim 1, characterized in that, The antioxidant is selected from one or two of 2,6-di-tert-butyl-4-methylphenol and triphenyl phosphite.
3. A method of using a modified polyester powder coating as described in any one of claims 1-2, characterized in that, Includes the following steps: A1. The film-forming acid component, epoxy curing component, modifier, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, antioxidant, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate and triphenylphosphine are added to a high-speed mixer and premixed at 600-1200 r / min for 6-15 min to obtain a premix. A2. The premixed material is added to a twin-screw extruder for melt extrusion. The temperature of the twin-screw extruder is 75-90℃ in zone 1, 90-105℃ in zone 2, 100-115℃ in zone 3, and 95-110℃ at the die head. The screw speed is 180-350 r / min, and the material residence time is 45-120 s to obtain the melt extrudate. A3. The molten extrudate is cooled by pressing, with the temperature of the cooling roller controlled at 10-25℃ and the sheet thickness at 0.8-2.0mm. After cooling, it is crushed to obtain sheet material. A4. The sheet material is pulverized by airflow and then sieved to remove coarse powder that does not pass through a 120-mesh sieve and fine powder that passes through a 200-mesh sieve. The powder that passes through a 120-mesh sieve but does not pass through a 200-mesh sieve is collected to obtain modified polyester powder coating. A5. Electrostatically spray the modified polyester powder coating onto the surface of a metal substrate that has been degreased, derusted, or phosphated. The spraying voltage is 40-80kV, the coating thickness is 60-100μm, and the coating is cured at 180-200℃ for 10-20min to obtain the modified polyester powder coating.
4. The method of using a modified polyester powder coating according to claim 3, characterized in that, In step A2, the modifier and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate are first added to a pre-dispersion container and pre-dispersed at 300-700 r / min for 4-10 min.
5. The method of using a modified polyester powder coating according to claim 3, characterized in that, In step A3, the molten extrudate is introduced into a cooling tableting device for tableting and cooling within 30 seconds. The cooling roller temperature of the cooling tableting device is 8-22℃, the roller spacing is 0.6-1.5mm, and the tableting roller speed is 12-35r / min.
6. The method of using a modified polyester powder coating according to claim 3, characterized in that, In step A4, the sheet material obtained in step A3 is subjected to airflow pulverization under the conditions of an inlet air temperature of 10-25℃, a classifying wheel speed of 1800-3200 r / min, and a pulverizing pressure of 0.45-0.75 MPa.
Citation Information
Patent Citations
High-weather-resistance powder coating and preparation method thereof
CN117683443A
Weather-resistant powder coating for doors and windows and preparation method of weather-resistant powder coating
CN121895837A